Complement Factor H-Related Protein 4A Is the Dominant Circulating Splice Variant of CFHR4 - Pouw, Richard B.; Brouwer, Mieke C.; van Beek, Anna E.; Józsi, Mihály; Wouters, Diana; Kuijpers, Taco W. (Frontiers in Immunology, 2018)
Recent research has elucidated circulating levels of almost all factor H-related (FHR) proteins. Some of these proteins are hypothesized to act as antagonists of the important complement regulator factor H (FH), fine-tuning complement regulation on human surfaces. For the CFHR4 splice variants FHR-4A and FHR-4B the individual circulating levels are unknown, with only total levels being described. Specific reagents for FHR-4A or FHR-4B are lacking due to the fact that the unique domains in FHR-4A show high sequence similarity with FHR-4B, making it challenging to distinguish them. We developed an assay that specifically measures FHR-4A using novel, well characterized monoclonal antibodies (mAbs) that target unique domains in FHR-4A only. Using various FHR-4A/FHR-4B specific mAbs, no FHR-4B was identified in any of the serum samples tested. The results demonstrate that FHR-4A is the dominant splice variant of CFHR4 in the circulation, while casting doubt on the presence of FHR-4B. FHR-4A levels (avg. 2.55 +/- 1.46 µg/mL) were within the range of most of the previously reported levels for all other FHRs. FHR-4A was found to be highly variable among the population, suggesting a strong genetic regulation. These results shed light on the physiological relevance of the previously proposed role of FHR-4A and FHR-4B as antagonists of FH in the circulation.